Immunohistological study of tight junction protein expression in mal de Meleda. (3rd July 2016) - Kacem, Monia; Agili, Faouzia; Tounsi, Haifa; Zribi, Hela; Zaraa, Ines; Mokni, Mourad; Boubaker, Samir
ABSTRACT: Mal de Meleda (MdM, MIM: 248300) is a rare autosomal recessive skin disorder characterized by diffuse palmoplantar keratoderma and transgressive keratosis with onset in early infancy. The gene responsible for MdM, ARS, encodes for Secreted Lys6/Plaur domain-containing protein 1 which is essential for epidermal homeostasis. Tight junctions have been proposed to have two mutually exclusive functions: a fence function which prevents the mixing of membrane proteins between the apical and basolateral membranes; and a gate function which controls the paracellular passage of ions and solutes between cells. In this study we report immunohistochemical investigations of tight junction proteins claudin-1 and occludin in MdM Tunisian families. Nine skin biopsies from patients with MdM were analyzed. The control group was formed by skin biopsies belonging to healthy individuals. Immunohistochemical study was performed on fixed sections from biopsies of four microns with the following polyclonal antibodies: anti-claudin-1 and anti-occludin. In control skin, claudin-1 exhibited membrane expression throughout the epidermis with increasing and upward intensity, whereas occludin was detected in the cell membrane of keratinocytes of the stratum granulosum. In MdM skin, claudin-1 was expressed throughout the thickness of the spinous layers with membrane staining, and occludin had cytoplasmic staining in the granular layer. The immunohistochemical expression of TJ proteins in MdM patients harbors premature expression of occludin and decreased expression of claudin-1, highlighting further evidence for disorders in epidermal homeostasis.